2011
DOI: 10.5194/nhess-11-145-2011
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric circulation patterns associated with strong wind events in Catalonia

Abstract: Abstract. The benefit of having a daily synoptic weather type catalogue and even more, a detailed catalogue for high impact weather events is well recognised by both climatologist and meteorologist communities. In this way the Meteorological Service of Catalonia (SMC) has produced some accurate classifications for extreme events, such as hailstorms or strong winds (SW). Within the framework of the MEDEX project, the SMC has been collaborating to increase the level of awareness about these events. Following thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 38 publications
(45 reference statements)
0
18
0
1
Order By: Relevance
“…It is well‐known that the clustering methods are unsupervised techniques, because they seek to partition the observations into a pre‐specified number of clusters subjectively defined. To identify the observations that could have been incorrectly classified, the outcome of CA was validated using a LDA (Venables and Ripley, ; Peña et al , ); some applications of the use of LDA can be found in Lawson and Cerveny () and Ward and Folland (). The LDA applied was based on the moment's method (Wilks, ).…”
Section: Methodsmentioning
confidence: 99%
“…It is well‐known that the clustering methods are unsupervised techniques, because they seek to partition the observations into a pre‐specified number of clusters subjectively defined. To identify the observations that could have been incorrectly classified, the outcome of CA was validated using a LDA (Venables and Ripley, ; Peña et al , ); some applications of the use of LDA can be found in Lawson and Cerveny () and Ward and Folland (). The LDA applied was based on the moment's method (Wilks, ).…”
Section: Methodsmentioning
confidence: 99%
“…Section 3 outlines the application of EOF analysis to detect the spatial and temporal occurrence of CAP (Lundquist et al, ). Synoptic situations associated with CAP and no‐CAP days are then characterized using a combination of principal component analysis (PCA), cluster analysis (CA) and discriminant analysis (DA) (Aran et al, ; Peña et al, ). Section 4 presents the results both spatially in terms of CAP distribution, and temporally in terms of appropriate synoptic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Even though a discrete number of atmospheric circulation types are unable to account for the full dynamics of the atmospheric continuum system, they have proved useful in understanding the regional and local climate variability of surface variables. Atmospheric circulation types in several regions globally have been linked to surface variables such as surface level ozone concentrations (Cooter et al 2007;Saavedra et al 2012), aerosol optical depths and concentrations of PM 10 (Zhang et al 2012), air temperature (Hoy et al 2013), cold spells (Guentchev and Winkler 2010), rainfall (Hope et al 2006;Raziei et al 2012;Romero et al 1999), flooding (Prudhomme and Genevier 2011), extreme surface winds (Peña et al 2011), and biological indicators such as potato yield (Sepp and Saue 2012). Our interest in the daily atmospheric circulation types (CTs) lies in extracting recurring daily types that could be used in future statistical-dynamical downscaling studies to develop high resolution wind climate maps at the mesoscale which are required to determine those areas that are best suited for wind farm development.…”
Section: Introductionmentioning
confidence: 99%